Análisis de las estrategias para la exportación de la resina de cannabis desde Colombia hacia países bajos. (2021)
Sativa cannabis has become one of the business growth tools with the greatest impact in European countries, but with a notorious impact in Latin American countries such as Colombia, given that due to the antecedents of the armed conflict, there are crops of cannabis, as well as the ecosystem variants to produce the plant in massive quantities.